Analysis of Implementation of Fixed Assets At The Youth And Sports Department of Padang City, West Sumatera Province - Desmiwerita, Desmiwerita (Dinasti Publisher, 2022)
In general, the measurement of fixed assets carried out by the Youth and Sports Office of West Sumatra Province is in accordance with Government Accounting Standards. According to Governmental Accounting Standards, the initial measurement of property, plant and equipment is measured at cost. Likewise, the measurement of fixed assets carried out by the Youth and Sports Office of West Sumatra Province is also measured based on historical costs and uses the services of a third party in revaluing assets / Appraisal of Regional Property Valuation. According to the Youth and Sports Office of West Sumatra Province, fixed assets obtained from donations are recognized in the relevant period, namely when the assets are received and the ownership rights are transferred. This is in accordance with Government Accounting Standards that an asset can be recognized as belonging to the entity if it is proven that it has become a transfer of ownership rights supported by legal evidence. In its fixed asset accounting policy, the Department of Youth and Sports of West Sumatra Province has depreciated its fixed assets. It is also in accordance with Government Accounting Standards. In the Government Accounting Standard Statement No. 7 paragraph 57 states that “other than land and construction in progress, all property, plant and equipment can be depreciated according to the nature and characteristics of the asset.